INTEGRATIVE APPROACH: PARADIGMATIC AND IMPLEMENTATIVE REVIEWS IN LEARNING FIQIH IN MADRASAH IBTIDAIYAH - Siti Mutma'inah (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2017)
This study discusses the Integrative Approach: Paradigmative and Implementative Review in Fikih Learning. The purpose of this study is to describe and analyze the integrative paradigm and its implementation in learning Fikih in Madrasah Ibtidaiyah. The research method used is qualitative approach with analytical descriptive method. The result of research stated that the learning of Islamic Religious Education, including Fikih need to contain approach and paradigm of integrative science, so that the learning process delivered by the teacher becomes intact, and not separating each other from one science to another. Fikih subjects are no longer just normative but also scientific. Understanding that resulted from integrative Fikih learning will lead learners to learn in totality, and make Fikih as a part of real life needed by them.